2020
DOI: 10.3389/fneur.2020.602102
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Daratumumab in a Patient With Severe Refractory Anti-NMDA Receptor Encephalitis

Abstract: Anti-NMDA receptor encephalitis is the most common type of antibody mediated autoimmune encephalitis (AIE). Patients often develop neuropsychiatric symptoms and seizures, women are affected about four times more than men, and in about 50% the disease is associated with a neoplasia, especially teratomas of the ovary. We describe the case of a 20-year-old woman suffering from a severe therapy refractory course of anti-NMDA receptor encephalitis. Treatment included glucocorticoids, plasma exchange, intravenous im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…Regarding other autoimmune disease, the administration of daratumumab in two patients with refractory lupus was recently described exhibiting clinical responses associated with significant depletion of long-lived plasma cells and modulation of effector T-cell responses ( 80 ). As regard as autoimmune encephalitis, targeting CD38 was achieved with daratumumab in one case of life-threatening anti-NMDA receptor encephalitis and in one case of refractory anti-CASPR2 encephalitis with improvements of neurological sequelae ( 81 , 82 ). In the last case, severe septicemia leading to patient death highlight an unmet need of rigorous clinical investigation to determine the efficacy and tolerance of CD38-targeting agent in autoimmune disease.…”
Section: Cd38 Antibodies In Solid Organ Transplantationmentioning
confidence: 99%
“…Regarding other autoimmune disease, the administration of daratumumab in two patients with refractory lupus was recently described exhibiting clinical responses associated with significant depletion of long-lived plasma cells and modulation of effector T-cell responses ( 80 ). As regard as autoimmune encephalitis, targeting CD38 was achieved with daratumumab in one case of life-threatening anti-NMDA receptor encephalitis and in one case of refractory anti-CASPR2 encephalitis with improvements of neurological sequelae ( 81 , 82 ). In the last case, severe septicemia leading to patient death highlight an unmet need of rigorous clinical investigation to determine the efficacy and tolerance of CD38-targeting agent in autoimmune disease.…”
Section: Cd38 Antibodies In Solid Organ Transplantationmentioning
confidence: 99%
“…Research in CD38 −/− mice found that CD38 deficiency ameliorated the course of pristane-induced lupus [14]. Because CD38 is expressed constitutively at high levels on human antibody-secreting plasmablasts and plasma cells and is inducible on several immune cell subsets upon activation, CD38 has been considered as a potential therapeutic target in autoantibodydriven diseases such as SLE [15], autoimmune encephalitis [16,17], and autoimmune hemolysis [18]. We recently treated two patients with refractory, life-threatening SLE with the anti-CD38 antibody daratumumab, which resulted in substantial clinical and immunological efficacy [11].…”
Section: Introductionmentioning
confidence: 99%
“…In mycobacterial infections due to anti-IFN-γ auto-antibodies, another phenocopy of an inborn error of immunity, rituximab has been used with success [ 69 73 ]. Depletion of plasmablasts can be achieved by antibodies targeting CD38 (e.g., daratumumab); the latter has been successfully used to treat multiple myeloma [ 74 ], autoimmune cytopenias [ 75 ], autoimmune organ diseases [ 76 , 77 ], and infection due to auto-Abs to cytokines [ 78 ]. These depletive therapies have not been studied as acute treatment for COVID-19 in the context of RCT or, to our knowledge, even published as case reports.…”
Section: B Cell and Plasmablast Depletion And Btk Inhibition: How About Covid?mentioning
confidence: 99%